Illness and therapy : spiritual-scientific aspects of healing : nine lectures given to physicians and medical students in Dornach between 11 and 18 April 1921 including Rudolf Steiner's notes for the lectures /: spiritual-scientific aspects of healing : nine lectures given to physicians and medical students in Dornach between 11 and 18 April 1921 including Rudolf Steiner's notes for the lectures. (2013) - Steiner, Rudolf, 1861-1925
No abstract available